2015
DOI: 10.3109/09638288.2015.1106600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a training in the Disability Assessment Structured Interview on the interviews of Dutch insurance physicians

Abstract: The DASI training improved the quality of assessment interviews of IPs. A semi-structured interview, like the DASI, can help physicians to pay more attention to activity limitations and participation in addition to medical information. Implications for Rehabilitation Experienced IPs are able to change their disability assessment interview routine after training. In determining work ability, IPs should pay more attention to claimant's activity limitations and participation in addition to medical information. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…This is all the more significant as functional interviewing has the potential to improve agreement in more vague data situations. However, it is noteworthy that other studies observed that functional interviewing detected more activity limitations (28,29).…”
Section: Strengths and Limitationsmentioning
confidence: 81%
“…This is all the more significant as functional interviewing has the potential to improve agreement in more vague data situations. However, it is noteworthy that other studies observed that functional interviewing detected more activity limitations (28,29).…”
Section: Strengths and Limitationsmentioning
confidence: 81%
“…A recent systematic review by Barth et al [35] supported this hypothesis demonstrating a high variation in judgements on work disability among medical examiners; using standardised assessment methods, like rating instruments for functional limitations or structured interview methods (such as the disability assessment structured interview (DASI) [36]), demonstrated a reduction in “inter-rater variability” and improved the reproducibility among examiners.…”
Section: Discussionmentioning
confidence: 99%
“…Uit verricht onderzoek blijkt dat de visie van de cliënt over de eigen belemmeringen niet altijd even goed wordt uitgevraagd. [1][2][3] Het is wel zinvol om een concreet beeld te hebben welke belemmeringen de cliënt zelf ervaart om een aantal redenen, onder andere:…”
Section: Inleidingunclassified